2011
DOI: 10.1111/j.1365-246x.2011.05153.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lithospheric magnetization in vector spherical harmonics

Abstract: S U M M A R YThe lithospheric contribution to the geomagnetic field arises from magnetized rocks in a thin shell at the Earth's surface. The lithospheric field can be calculated as an integral of the distribution of magnetization using standard results from potential theory. Inversion of the magnetic field for the magnetization suffers from a fundamental non-uniqueness: many important distributions of magnetization yield no potential magnetic field outside the shell. We represent the vertically integrated magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 11 publications
1
60
0
Order By: Relevance
“…Gubbins et al 2011) due to source distributions that give no external field (the magnetic annihilators that were exemplified by Runcorn 1975). The deterministic studies explain many of the magnetic field structures observed at the satellite altitudes but they rarely account accurately for all the observed features in space.…”
Section: Introductionmentioning
confidence: 99%
“…Gubbins et al 2011) due to source distributions that give no external field (the magnetic annihilators that were exemplified by Runcorn 1975). The deterministic studies explain many of the magnetic field structures observed at the satellite altitudes but they rarely account accurately for all the observed features in space.…”
Section: Introductionmentioning
confidence: 99%
“…From Remark 2.2, it becomes clear that the spherical decomposition of Theorem 2.1 reveals the desired properties corresponding to the thin-plate case in Theorem 1.4(a),(b) (which has already been observed in [13]). …”
Section: Vector Spherical Harmonic Representationmentioning
confidence: 85%
“…n,k (see, e.g., [1,13,18,19,22]). These vector spherical harmonics can be defined via a suitable connection to the inner harmonics H int n,k and the outer harmonics H ext n,k (i.e., the harmonic extensions of scalar orthonormalized spherical harmonics Y n,k into Ω int and Ω ext , respectively).…”
Section: Vector Spherical Harmonic Representationmentioning
confidence: 99%
See 2 more Smart Citations